CARCASS PERCENTAGE AND COMMERCIAL CARCASS PARTS THE JAPANESE QUAILS GIVEN TUMERIC EXSTRAC IN THE DRINKING WATER - N. W. Y. M., Pusari; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the effect ofthe effect of giving turmeric extrack to drinking  water of quails on the percentage of carcass and commercial carcass parts.  The research design used was a completely randomized design (CRD) consisting of 3 treatments and 6 replications, each replication containing 3 quails. Consisting of R0: quail given drinking water without turmeric extract (control), R1: quail given drinking water plus 1% turmeric extract, R2: Quail given drinking water plus 2% turmeric extract. The turmeric used in this study is the turmeric rhizome. The variables observed were slaughter weight, carcass weight, carcass percentage, and carcass cuts percentage which included chest, upper thigh, lower thigh, wing, and back. The results showed that quails that were given turmeric extract as much as 1% and 2% in drinking water had slaughter weights, carcass weights, carcass percentages, and commercial carcass cut percentages which were not significantly different (P>0.05) compared to controls.  Based on the results of this study, it can be concluded that the use of 1% and 2% turmeric extract in drinking water did not affect slaughter weight, carcass weight, carcass percentage, and carcass pieces of 8 weeks old quail.   Keywords: turmeric extract, quail, carcass , commercial carcass cuts